Hemoglobin Regeneration and Distribution of Iron, Copper and Zinc in Hepatic Subcelluler Frantions of Rats Fed With Tempe Diets - Mary Astuti; Seiichi Kasaoka; Shiro Goto; Mochamad Adnan (Indonesian Association of Food Technologists, 1994)
Hemoglobin regeneration efficiency was used to predict the iron availability of tempe diet by the method of depletion and repletion using rats for animal experiment. Hemoglobin regeneration efficiency of tempe showed the same effect with casein diet and unfermented soybean diet indicating that iron from soybeans are a good source of available iron. Iron, copper, and zinc from casein, unfermented soybean and tempe diets were distributed in hepatic subcelluler fractions in the same pattern. The highest level of iron and zinc were found in the cytosolic fraction and copper was found in the nuclear fraction. The different pattern among those trace minerals indicates that they have distinct roles in hemoglobin synthesis and metabolism.